REVISITING THE BASIC READING TEXTBOOK SYLLABUS BY INSERTING SUSTAINABLE DEVELOPMENT GOALS THEMES - Eva Nurul Candra (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThe Basic Reading Syllabus has an important role in teaching reading. It contains the text types that should be taught for the students. Text is one of the prominent tools in teaching reading since the purpose of reading activity is to get information from the text. By the changing of global situation, the basic reading syllabus should adapt the theme of the text that appropriate with the recent world. One of the issues which spread out all over the world is about Sustainable Development Goals (SDGs). It is a universal call to end poverty, protect the planet and ensure that all people to have a better life. Through the syllabus, teachers can measure how far the effectiveness and renewal of a teaching material are. Therefore, the objective of this research was to analyze whether the Basic Reading textbook needed some revisiting in order to be relevant to SDGs criteria in its texts. Engaged by 55 students of the third semester and 8 lecturers who taught Basic Reading, the data were collected by giving questionnaires and were analyzed qualitatively. The research has found that the text in the Basic Reading textbook had 10% for the Suitable Environment dimension, which could be classified as poor. Suitable environment is considered as the Sustainable Development Goals content. By considering this finding, the text in the Basic Reading textbook needs to be improved by inserting of Sustainable Development Goals theme. In other words, the Basic Reading text syllabus needs to be revisited. Keywords: basic reading textbook, sustainable development goals, revisiting syllabus